2016
DOI: 10.1098/rsbl.2015.1043
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic association of rotifer Philodina roseola with the branchiuran fish ectoparasite Argulus bengalensis at its embryonic stage

Abstract: Several rotifers including Philodina spp. are well known to make commensal and parasitic associations with different animals. The present investigation was carried out to decipher the relationship of Philodina roseola with a piscine ectoparasite Argulus bengalensis in its embryonic stage. Mechanical removal of the symbiont P. roseola from the argulid egg strips resulted in the complete (100%) failure in hatching. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…To date, only one example of rotifers remaining in a mutualistic relationship was described, and it concerned the bdelloid rotifer Philodina roseola feeding on the jelly coat covering the eggs of the fish ectoparasite Argulus bengalensis , which enable the larvae to hatch (Banerjee et al . 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one example of rotifers remaining in a mutualistic relationship was described, and it concerned the bdelloid rotifer Philodina roseola feeding on the jelly coat covering the eggs of the fish ectoparasite Argulus bengalensis , which enable the larvae to hatch (Banerjee et al . 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few parasite embryos have ever had mutualistic symbionts, but Banerjee et al (2016) have found one. A rotifer, Philodina roseola Ehrenberg, 1832, feeds off the jelly coat of the egg strips of Argulus bengalensis Ramakrishna, 1951.…”
Section: Life Cyclementioning
confidence: 99%
“…7). Banerjee's et al (2016) mutualistic rotifer has obviously co-evolved with Argulus bengalensis. We suggest that at one point, the rotifer appears to have been a hyperparasite (many in its genus are parasites) or predator harming the egg strip.…”
Section: Life Cyclementioning
confidence: 99%